Peran Teknologi Blockchain dalam Meningkatkan Kepercayaan Konsumen dan Keamanan Data Privasi pada Platform E-Commerce di Indonesia - Lisdayanti, Annisa; Padmanegara, Oliver Hasan (https://jurnal.binamandiri.ac.id/, 2024)
This study examines the role of blockchain technology in enhancing consumer trust and data privacy security on e-commerce platforms in Indonesia. The rapid growth of e-commerce in Indonesia has transformed shopping patterns and economic interactions, but it has also raised concerns regarding data security and privacy. Through a systematic literature review of recent research (2017-2023), this study identifies key factors influencing consumer trust in e-commerce, including website quality, vendor reputation, and transaction security. The study also investigates the potential of blockchain technology to address trust and data security issues on e-commerce platforms. The findings suggest that blockchain can improve transaction transparency, security, and efficiency, though its implementation still faces technical and regulatory challenges. This study highlights the importance of a holistic approach in building consumer trust, involving technical, social, and psychological aspects. The implications of this research provide valuable insights for e-commerce platform developers, policymakers, and researchers in the fields of technology and consumer behavior.